Relation between parent and child or peer alienation and life satisfaction: The mediation roles of mental resilience and self-concept clarity - Chen, Na; Jing, Yuanluo; Pang, Yazhi (Frontiers in Psychology, 2022)
The research on life satisfaction originated in the 1960s and has not been completely studied yet. Life satisfaction is an index related to the state and quality of individual life. With the development of society, the relevant variables affecting life satisfaction have also changed with the times. The purpose of this study is to research the relationship between parent and child or peer alienation, mental resilience, self-concept clarity and life satisfaction, finding the mechanism of action among parent-child or peer alienation, mental resilience, self-concept clarity, and life satisfaction. This cross-sectional study recruites randomly 1,347 adolescents from six middle schools in Chongqing, China, participating in a questionnaire on sociodemographic characteristics, the Inventor of Parent and Peer Attachment (IPPA), the Connor-Davidson Resilience Scale (CD-RISC-10), the Self-concept Clarity Scale (SCCS), and the Satisfaction with Life Scale (SWLS). The sample consists of 62.4% female participants (n = 841) and 37.6% male participants (n = 506) aged from 11 to 17 years old (Mean = 14.54, SD = 1.21). We use SPSS 26 to perform the statistical analysis. The study finds that mental resilience—self-concept clarity have mediating effect on the parent or peer alienation to life satisfaction, to the effect that, parent-child or peer alienation explain life satisfaction through the chain mediating effect of mental resilience—self-concept clarity. This study explores the negative multi-use of parent-child or peer alienation on life satisfaction and provides a new perspective for the improvement of life satisfaction of adolescents.